Environmental and correlative significance of a non-marine algal limestone (Westphalian D), Sydney Coalfield, Cape Breton Island, Nova Scotia - Vasey, Gary; Zodrow, Erwin (Atlantic Geology, 1983)
The occurrence of an algal limestone containing stromatolites within the Morien Group (Sydney Coalfield) is reported for the first time. Three distinct morphologic forms of stromatolite (pinnacle, mat and detached) and their stratigraphic variation are described. Variation in clast type and size, biota and elements within the algal limestone is interpreted as evidence for the growth of stromatolites on the shore of an ephemeral, fresh to brackish lake, subject to fluctuating water levels. Pinnacle and mat forms developed on substrate irregularities. A bivalve and ostracode fauna in mudatones and siltstones above and below the algal limestone indicates a correlation with the Anthraconauta tenuis chronozone of Britain (Westphalian D) and corroborates on age derived from associated macro- and microflora.